2002
DOI: 10.1046/j.1365-2133.2002.04920.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of a psoriasis care instruction programme with dithranol compared with UVB phototherapy and inpatient dithranol treatment

Abstract: Summary Background This study was part of a large national cost‐effectiveness analysis, and was funded by the National Fund for Investigational Medicine of the Health Care Insurance Board. Objectives To compare the costs of treatment of moderate to severe psoriasis by dithranol short contact therapy in a care instruction programme (short contact therapy) with ultraviolet B phototherapy (UVB) and inpatient dithranol treatment (inpatient treatment), and relate these costs to treatment effectiveness. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…A study about a new combined outpatient and hometreatment of psoriasis technology showed that 89% of the anticipated savings, based on the outcomes of an earlier performed cost-effectiveness analysis, could not be achieved in the short run when implementing this technology due to inflexibility of production factors labor and infrastructure [2,12]. In absolute figures this meant that only D 694 of the anticipated D 6058 savings per patient could be freed and consequently over D 5000 per patient could not be re-invested in the outpatient and home-treatment in the short run.…”
Section: Unanticipated Losses On the Short Runmentioning
confidence: 99%
“…A study about a new combined outpatient and hometreatment of psoriasis technology showed that 89% of the anticipated savings, based on the outcomes of an earlier performed cost-effectiveness analysis, could not be achieved in the short run when implementing this technology due to inflexibility of production factors labor and infrastructure [2,12]. In absolute figures this meant that only D 694 of the anticipated D 6058 savings per patient could be freed and consequently over D 5000 per patient could not be re-invested in the outpatient and home-treatment in the short run.…”
Section: Unanticipated Losses On the Short Runmentioning
confidence: 99%
“…192 The model uses data from the Netherlands to estimate the health service costs of treating moderate-to-severe psoriasis if biologics are not used or patients do not respond to biologics. 188 It is assumed that there is no progression of HAQ for patients using biologics, based on elicitation of opinion from experts. There is considerable uncertainty about the 'rebound' of HAQ after withdrawal.…”
Section: Systematic Review Of Existing Cost-effectiveness Evidence)mentioning
confidence: 99%
“…Our assumption is confirmed by Bickers et al [1], who published inpatient treatment costs for psoriasis in the USA of USD 6 million, in a country with a population 40 times larger. However, it is important to state that hospitalization for psoriasis in the USA is much less frequent than in Europe [11]. Nearly two thirds of the cases were grouped into the DRG J61B.…”
Section: Discussionmentioning
confidence: 99%